Platelet-derived microRNA-223 attenuates TNF-α induced monocytes adhesion to arterial endothelium by targeting ICAM-1 in Kawasaki disease - Guo, Manli; Fan, Shunyang; Chen, Qian; Jia, Cuiping; Qiu, Miaoyun; Bu, Yun; Tang, Wai Ho; Zhang, Yuan (Frontiers in Immunology, 2022)
Background Kawasaki disease (KD) is an acute vasculitis that may result in permanent coronary artery damage with unknown etiology. Endothelial cell (EC) dysfunction and platelet hyperactivity are the hallmarks of KD. Platelets are involved in the development of endothelial dysfunction. MiR-223 transferred by platelet microparticles (PMPs) has been found to involve in the functional regulation of endothelial cells in sepsis. However, the role of platelet-derived miR-223 in endothelial dysfunction has not yet been investigated in KD. Objectives We seek to investigate the role of platelet-derived miR-223 in endothelial dysfunction of KD vasculopathy. Methods and results Forty-five acute KD patients and 45 matched controls were randomly recruited in the study. When co-cultured with human coronary artery endothelial cells (HCAECs), KD platelets with higher levels of miR-223 were incorporated into HCAECs, resulting in the horizontal transfer of miR-223. Using KD platelets, PMPs, and platelet-releasate from the same amount of blood co-cultured with HCAECs, we found the increased expression of miR-223 in HCAECs was primarily derived from KD platelets, rather than PMPs or free miRNAs from platelet- releasate. KD platelet-derived miR-223 attenuated TNF-α induced intercellular cell adhesion molecule-1 (ICAM-1) expression in HCAECs. KD platelet-derived miR-223 also suppressed the monocyte adhesion to HCAECs. In vivo, platelet-specific miR-223 knockout (PF4-cre: miR-223flox/flox) C57BL/6 mice and miR-223flox/flox C57BL/6 mice were used. Using Lactobacillus casei cell wall extract (LCWE) to establish KD murine model, we showed that in LCWE-injected PF4-cre: miR-223flox/flox mice, deficiency of platelet-miR-223 exacerbates the medial thickening of the abdominal aorta, increased ICAM-1 expression with concomitant CD45+ inflammatory cells infiltration into the endothelium compared to LCWE-injected miR-223flox/flox mice. Conclusions The horizontal transfer of platelet-derived miR-223 suppresses the expression of ICAM-1 in HCAECs, which at least in part attenuates leukocyte adhesion, thereby reducing endothelial damage in KD vasculitis